KONTRIBUSI HUTAN PINUS RAKYAT TERHADAP PENDAPATAN MASYARAKAT DI TANA TORAJA - Daud Malamassam (PERENNIAL, 2007)
A study on the contribution of community forest to the community income in Tana Toraja Regency was implemented with the aim of identifying the community forest contribution to owners income and formulating the effort that can be carried out for enhancing the contribution. As the result, the community forest contribution to owners income is still very low (2.94% in average). Based on analysis result, the potencial revenue of community forest farming in Tana Toraja Regency can be 2.3 larger than the present obtaining revenue. The mentioned potencial revenue can be more increased by developing a more proportional allocation of the revenue to the related farmers (related communities) Key words : Community forest, contribution, community income, forest product and benefit